MPLS and traffic engineering in IP networks. - Awduche, D.O (IEEE Communications magazine)
Rapid growth and increasing requirements for service quality, reliability, and efficiency have made traffic engineering an essential consideration in the design and operation of large public Internet backbone networks. Internet traffic engineering addresses the issue of performance optimization of operational networks. A paramount objective of Internet traffic engineering is to facilitate the transport of IP traffic through a given network in the most efficient, reliable, and expeditious manner possible. Historically, traffic engineering in the Internet has been hampered by the limited functional capabilities of conventional IP technologies. Recent developments in multiprotocol label switching (MPLS) and differentiated services have opened up new possibilities to address some of the limitations of the conventional technologies. This article discusses the applications of MPLS to traffic engineering in IP networks